Systematic review of the links between eco-distress and mental health - Gebhardt, Nadja; Westermann, F.; Kleinböhl, Lilli; Friederich, Hans-Christoph; Nikendei, Christoph (EcoHealth, 2025)
Eco-distress shows positive correlations with mental health impairments. However, the correlations reported by different studies vary widely. The aim of our review was to explore possible methodological sources for this heterogeneity, hereby deepening our understanding of eco-distress and its relationship with mental health.